Maritime Conservation Area during COVID-19 Pandemic: The Case of Benoa Bay Bali - Subekti Slamet (EDP Sciences, 2021)
The COVID-19 pandemic has had a wide impact on the lives of the Balinese people. The purpose of this study is to find sources of food security related to the status of Benoa Bay as a Maritime Conservation Area (MCA) during the COVID-19 pandemic, thus providing alternative livelihoods for local communities. The research is based on published secondary data collected from observations processed descriptively. The results show that local wisdom plays an important role in maintaining Benoa Bay as a sacred area for religious and cultural activities, and secondly that the determination of Benoa Bay as an MCA is strategic in managing maritime cultural areas within the framework of SDG 14, which has an impact on creating social inclusion, improving the welfare of local communities and ensuring the sustainability of marine ecosystems in the coastal areas of Bali. The third finding is that the spread of the COVID-19 pandemic is due to the high level of population mobility and the population structure of Bali, which is already relatively old and has the potential to accelerate the potential for high case fatality rates from the pandemic. Fourth, Benoa Bay has potential resources as alternative livelihoods for local communities during the COVID-19 pandemic. Based on the study results, it is recommended to tighten the possibility of spreading through the first and second rapid tests involving as many people as possible as carriers of the spread of COVID-19, both through local transmission and imported cases. Furthermore, indigenous peoples are recommended to consistently fight for the status of Benoa Bay as an MCA through a Presidential Regulation (Peraturan Presiden) to ensure the preservation of the maritime ecosystem with its potential resources.